Термобарогеохимическая характеристика некоторых золотоносных участков центральной части Украинского щита - Лазаренко, Е.Е.; Блажко, В.И.; Фомин, Ю.А. (Видавничий дім "Академперіодика" НАН України, 2008)
The results of thermobarogeochemical investigations of epigenetic quartz and host rocks of some gold-bearing districts in the Central Part of the Ukrainian Shield are presented. The process of gold-quartz-sulfide zone formation was hydrothermal by nature and passed in the temperature interval 455–120 ºС under conditions of the pressure downfall – 0.8–0.3 kbar. The most real temperature of the quartz deposit was probably 420–320 ºС.